Macroalgal meadow habitats support fish and fisheries in diverse tropical seascapes. Issue 4 (12th March 2020) - Fulton, Christopher J.; Berkström, Charlotte; Wilson, Shaun K.; Abesamis, Rene A.; Bradley, Michael; Åkerlund, Carolina; Barrett, Luke T.; Bucol, Abner A.; Chacin, Dinorah H.; Chong‐Seng, Karen M.; Coker, Darren J.; Depczynski, Martial; et al.
Abstract: Canopy‐forming macroalgae can construct extensive meadow habitats in tropical seascapes occupied by fishes that span a diversity of taxa, life‐history stages and ecological roles. Our synthesis assessed whether these tropical macroalgal habitats have unique fish assemblages, provide fish nurseries and support local fisheries. We also applied a meta‐analysis of independent surveys across 23 tropical reef locations in 11 countries to examine how macroalgal canopy condition is related to the abundance of macroalgal‐associated fishes. Over 627 fish species were documented in tropical macroalgal meadows, with 218 of these taxa exhibiting higher local abundance within this habitat (cf. nearby coral reef) during at least one life‐history stage. Major overlap (40%–43%) in local fish species richness among macroalgal and seagrass or coral reef habitats suggest macroalgal meadows may provide an important habitat refuge. Moreover, the prominence of juvenile fishes suggests macroalgal meadows facilitate the triphasic life cycle of many fishes occupying diverse tropical seascapes. Correlations between macroalgal canopy structure and juvenile abundance suggests macroalgal habitat condition can influence levels of replenishment in tropical fish populations, including the majority of macroalgal‐associated fishes that are targeted by commercial, subsistence or recreational fisheries. While many macroalgal‐associated fishery species are of minor commercial value, their local importance for food and livelihood security can be substantial (e.g. up to 60% of landings in Kenyan reef fisheries). Given that macroalgal canopy condition can vary substantially with sea temperature, there is a high likelihood that climate change will impact macroalgal‐associated fish and fisheries.